KEHADIRAN YANG SETIA DI RUANG PUBLIK - Joas Adiprasetya (Jurnal Teologi (Journal of Theology), 2022)
AbstractThis article investigates the possibility of the presence of the Church in the the public space through the presence of Christian persons in their various everyday spheres. By employing the dyadic understanding of abiding-and-go (Michael Gorman) and abiding-and-sending (the Generous Love document), I argue that Christians represent the whole church in their presence in the public space. In turn, by representing the whole church, Christians also make the Trinitarian communion present through their public engagement. As such, the church participates in God’s mission (missio Dei) both institutionally and personally.AbstraksiArtikel ini menyelidiki kemungkinan kehadiran Gereja di ruang publik melalui kehadiran orang-orang Kristen di berbagai ruang keseharian mereka. Dengan menggunakan pemahaman diadik tentang tinggal-dan-pergi (Michael Gorman) dan tinggal-dan-mengirim (dokumen Cinta yang Murah Hati), saya berpendapat bahwa orang Kristen mewakili seluruh gereja di hadapan mereka di ruang publik. Pada gilirannya, dengan mewakili seluruh gereja, orang Kristen juga menghadirkan persekutuan Tritunggal melalui keterlibatan publik mereka. Dengan demikian, gereja berpartisipasi dalam misi Tuhan (missio Dei) baik secara institusional maupun pribadi.